OBSERVING ILLOCUTION IN E-COMIC STRIP THE ADVENTURE OF TINTIN AND ITS IMPLICATION IN ENGLISH LANGUAGE TEACHING DURING THE PANDEMIC - Masykuri, Edi Sunjayanto; Nurhadi, Rofiq (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This research is about the direct and indirect directive and commissive illocution in The Adventure of Tintin movie. The aims of this research are to analyze direct and indirect directive and commissive illocution; to describe the application of teaching speaking by using direct and indirect directive and commissive illocution in the movie. Data collection techniques using observational studies. The result shows 42 utterances in the movie are categorized into the direct and indirect directive and commissive illocution in the movie. 35 utterances of direct-directive (83,7%) contains ask (19,35%), command (14,2%), request (19,35%), challenge (7%) and insist (23,8%), 2 utterances of indirect-directive (4,7%) contains command, 4 utterances of direct-commissive (9,3%) contains guarantee (2,3%) and promise (7%), and 1 utterance of indirect-commissive (2,3%) contains promise.